Mathematical Model for Calculation of Poverty Rate in Libya - Manfor, Lamien (Al-Mukhtar Journal of Sciences, 2005)
The maim purpose of this paper is to write a mathematical mode for calculating of poverty rate. The aim is also to look at the economic situation in Libya. Moreover, this paper encourages other researchers to approach this particular area of research, which is the economics of poverty. The paper is based on the mathematical; simulation of the model by using OLS as a way of estimating the equations of the model. The model has been programmed using (MatLab program) calculating different variable and parameters of the estimated model simultaneously. Two forms of the model were applied for the calculation of the poverty rate. The first one is with five variables while the other is with three variables. The findings show that 14% of Libyans lives under the poverty line. Data indicated also that living standards in Libya is better than those of most developing countries in the region. It is 22% in Tunisia, 30% in Nigeria and 38% in Egypt.